Risk Factors of Body Mass Index (BMI), Age of Menarche, Parity and Hormonal Contraception of Genu Osteoarthritis in Female Patients - Alisiya, Alisiya; Sulistiawati, Sulistiawati; Kurniawati, Patricia Maria; Wardhani, RR Indrayuni Lukitra (Folia Medica Indonesiana, 2021)
Osteoarthritis (OA) is a degenerative disease related to joint cartilage and commonly occurs in the knee joint. The 2013 National Survey recorded the prevalence of joint diseases in East Java was 26.9%. OA affected more women than men due to the estrogen and caused disabilities in many women. This study aimed to find the relationship between Body Mass Index (BMI), age of menarche, parity, and the use of hormonal contraceptives against OA in genu at Universitas Airlangga Hospital, Surabaya. This was an analytic observational study with a case-control approach. Data collection was carried out through a short interview using a questionnaire. The sample size was calculated using a formula and found that the study required 42 patients with OA in the case group and 42 patients without OA in the control group. The case group was dominated by patients with 56-60 years old age (62.1%), BMI 23-24.9 kg/m2 (58.7%), menarche age 12-13 years (53.6%), multiparous (52.6%), having contraception pill usage history (62.3%) particularly using combination pills (60.5%) with a mean duration of use > 1 year (56.8%). There was a relationship between BMI and type of hormonal contraceptive used against genu OA in female patients at Universitas Airlangga Hospital Surabaya.